2020
DOI: 10.1002/prot.25879
|View full text |Cite
|
Sign up to set email alerts
|

How good are comparative models in the understanding of protein dynamics?

Abstract: The 3D structure of a protein is essential to understand protein dynamics. If experimentally determined structure is unavailable, comparative models could be used to infer dynamics. However, the effectiveness of comparative models, compared to experimental structures, in inferring dynamics is not clear. To address this, we compared dynamics features of ~800 comparative models with their crystal structures using normal mode analysis. Average similarity in magnitude, direction, and correlation of residue motions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Lastly, the accuracy of computational models relies on sequence identity. Expected accuracies are low when identity of the sequence with its template is low [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the accuracy of computational models relies on sequence identity. Expected accuracies are low when identity of the sequence with its template is low [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The root mean square inner product (RMSIP) quantifies the similarity between sets of modes obtained from normal mode analysis by measuring the cumulative overlap of eigenvectors to quantify similarity in the directionality of residue motions. , Here, we computed the RMSIP between the lowest frequency modes of the stand-alone GCH1 of R. norvegicus and P.…”
Section: Methodsmentioning
confidence: 99%
“…The root mean square inner product (RMSIP) quantifies the similarity between sets of modes obtained from normal mode analysis by measuring the cumulative overlap of eigenvectors to quantify similarity in the directionality of residue motions. 66,67 Here, we computed the RMSIP between the lowest frequency modes of the stand-alone GCH1 of R. norvegicus and P. falciparum GCH1 homology model as well as the GCH1−GFRP inhibitory and stimulatory complexes. Therefore, the RMSIP is used to illustrate the overlap of the principal subspaces/set of modes between the structures.…”
Section: Journal Of Chemical Information and Modelingmentioning
confidence: 99%
“…Protein dynamics can be visualized by principal component analysis (PCA), which represents ensembles using a sequence of eigenvectors, whereby each eigenvector represents an aspect of protein motion by a phase space behavior 53 . PCA analysis (Fig.…”
Section: Structural Consequences By Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…5 ) showed the variances of variant structures differed from the wild-type. The similarities and differences between essential subspaces of wild-type and variant ensembles were highlighted by root mean square inner product (RMSIP) calculations 53 55 . Plots representing pairwise comparisons between the wild-type and variants suggested that the dynamic motions of the variants and wild-type differed, and substantial differences were observed for the first three principle components (PCs) (Fig.…”
Section: Structural Consequences By Molecular Dynamics (Md) Simulationmentioning
confidence: 99%